Need of vocational high school based on local potential for regional development in Cilacap District - Widi Lesmana; Pardjono Pardjono (Jurnal Pendidikan Vokasi, 2019)
This study intends to: (1) describe regional development programs, (2) determine local potential, (3) describe the level of alignment of the current spectrum of expertise and make a spectrum of expertise Vocational High Schools based local potential in the Cilacap District. Descriptive research was used in this study. The research site was carried out in the Cilacap Regency area. The data sources used are secondary data sources, namely the use of data through official documents such as the Rencana Tata Ruang Wilayah (RTRW), Rencana Pembangunan Jangka Menengah Daerah (RPJMD), Cilacap Regency in the 2017 Figures and the Cilacap Regency Economic Census in 2016. Analysis of official documents are used to achieve the research objectives. The validity of the documents carried out is the provision of a wet stamp from the related agency. The results of this study include: (1) the development program planned for the development of local potential in the Cilacap Regency area is listed on the 4th mission of regional development, namely "developing an economy that relies on local and regional potential"; (2) existing local potential includes the manufacturing sector; agriculture, forestry and fisheries; wholesale and retail trade, car and motorcycle repair; and the construction sector; (3) the level of alignment of the expertise spectrum of SMK with local potential in corridor 1 amounting to 35.7%; corridor 2 of 28.6%; corridor 3 is 43% while corridor 4 is 28.5%; areas of expertise that are in harmony with local potential include: Technology and Engineering; Agribusiness and Agrotechnology; Maritime; Business and management. The needs of local potential vocational schools are 36 schools, 465 classes and 887 teachers. It is necessary to close and increase the areas of expertise, expertise programs and expertise competencies to be in harmony with local potential in the Cilacap Regency and its surrounding areas.